CO2 capture using membrane contactors: a systematic literature review - Hafeez, Sanaa; Safdar, Tayeba; Pallari, Elena; Manos, George; Aristodemou, Elsa; Zhang, Zhien; Al-Salem, S. M.; Constantinou, Achilleas (My University, 2021)
With fossil fuel being the major source of energy, CO2 emission levels need to be reduced to a minimal amount namely from anthropogenic sources. Energy consumption is expected to rise by 48% in the next 30 years, and global warming is becoming an alarming issue which needs to be addressed on a thorough technical basis. Nonetheless, exploring CO2 capture using membrane contactor technology has shown great potential to be applied and utilised by industry to deal with post- and pre-combustion of CO2. A systematic review of the literature has been conducted to analyse and assess CO2 removal using membrane contactors for capturing techniques in industrial processes. The review began with a total of 2650 papers, which were obtained from three major databases, and then were excluded down to a final number of 525 papers following a defined set of criteria. The results showed that the use of hollow fibre membranes have demonstrated popularity, as well as the use of amine solvents for CO2 removal. This current systematic review in CO2 removal and capture is an important milestone in the synthesis of up to date research with the potential to serve as a benchmark databank for further research in similar areas of work. This study provides the first systematic enquiry in the evidence to research further sustainable methods to capture and separate CO2. [Figure not available: see fulltext.]
Keywords: Absorbent; CO2 capture; Membrane contactor; Preferred reporting items for systematic reviews and meta-analyses